FROM COLONIAL LEGACY TO MODERN CHALLENGES: THE SOCIO-ECONOMIC AND SECURITY IMPACTS OF FOREIGN WORKERS IN MALAYSIA - Zainol, Noor Azmi Mohd; Noor, Norazlin Che Mohd; Taib, Khairul Nizam; Sofian, Mohd Haniff; Salleh, Mohd Shaiful (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This research examines the effects of Malaysia’s influx of foreign workers, with particular emphasis on the socioeconomic and the security implications. The migration of foreign workers to Malaysia, particularly since the British colonial era, has shaped the nation’s multi-ethnic society and fuelled its economic growth. However, this migration has not come without challenges. The objective of this paper is to evaluate both the positive contributions and the negative effects of foreign labour on Malaysia’s economy, society, and security. While foreign workers have been essential in sectors such as construction, manufacturing, and agriculture, their increasing presence in other sectors, including retail, healthcare, and services, has raised concerns regarding employment opportunities for local workers, cultural assimilation, and national identity. Additionally, security issues such as the rise in crime, health risks, and exploitation have emerged as significant concerns. The research adopts a historical and contemporary analysis approach, utilizing qualitative method including government reports, census data, and case studies. The findings indicate that while foreign workers are vital to Malaysia’s economic development, their growing numbers have contributed to rising unemployment among Malaysians, social segregation, and an increase in criminal activities, particularly in urban areas. Furthermore, the outflow of money due to remittances from foreign workers has strained Malaysia’s economy. The study concludes that while foreign workers have played a pivotal role in shaping Malaysia’s growth, a balanced approach is needed to mitigate the adverse effects. This includes stricter immigration policies, promoting local workforce development, and addressing social integration challenges to ensure national cohesion and security in the face of increasing migration.